New Antihypertensive Drugs Under Development - Tamargo, J.; Duarte, J.; Ruilope, L.M. (Current Medicinal Chemistry, 2015)
Hypertension is the most common cardiovascular disease and remains the most prevalent risk factor for cardiovascular diseases and a major cause of death worldwide. Despite the large number of antihypertensive drugs available, in the majority of patients blood pressure still remains not optimally controlled and persists at high risk of cardiovascular complications. The limitations of current therapies have stimulated the research and development of new classes of antihypertensive agents, with different mechanisms of action, that provide a better blood pressure control, greater protection against organ damage, better tolerability and more effective prevention of cardiovascular diseases. However, essential hypertension is a multifactorial and multigenic disorder, which means that various mechanisms contribute to a greater or lesser extent to increase BP. Recent advances in the understanding of the multiple and complex cellular signalling pathways that modulate vascular smooth muscle cell contraction and growth involved in the regulation of vascular tone and in hypertension-induced end-organ damage have provided valuable insight in identifying new therapeutic targets. This article reviews new antihypertensive drugs under development, focusing on their mechanisms of action and possible advantages compared with traditional drugs.
Keywords: hypertension